Cytotoxic Effects of Methylgerambullin and Bis(Methylthiomethyl)-Disulphide (SB) on T-Lymphoblastic Leukemic Cell Line (Cem-SS) - Mohamed, Shar Mariam (2000)
The cytotoxic effects of 2 sulphur-containing compounds were studied on Tlymphoblastic leukemic cell line. Methylgerambullin is believed to be a new sulphone derived from a methylthiopropenoic acid isolated from Glycosmis calcicola (family Rutaceae). Another sui phonic compound IS bis- (methylthiomethyl)-disulphide, an extract from Scorodocarpus borneensis (family Olacaceae) with irritating garlic-like odor. Cytotoxic activities of methylgerambullin and bis-(methylthiomethyl)-disulphide were tested against CEM-SS (T-Iymphoblastic leukaemia), KU812F (chronic myelogeneous leukaemia), UACC-62 (melanoma) and HT29 (colon cancer) cell lines using MTT, a colorimetric tetrazolium-based assay. Cytotoxic concentrations of the compounds that killed cells by 50% (CD50) with respect to untreated cell population, varied among the cell lines tested. CEM-SS was found to be the most sensitive cell line to methylgerambullin and bis-(methylthiomethyl)-disulphide with CD50 = 0.25 )µg/ml and 3.50 )µg/ml respectively. The cytotoxic effects exerted by both compounds on this cell line was studied from both morphological manner over 72 hours period. Microscopic observations, including inverted microscopy of live cultures, fluorescent microscopy of acridine orange-propidium iodide stained cultures, and scanning and transmission electron microscopy showed that both necrotic and apoptotic death occurred in meiliylgerambullinand bis-(methylthiomethyl)-disulphide-treated cell populations, based on morphological criteria. From agarose gel electrophoresis and quantitative analyses of intemucleosomal cleavage, treatments with these compounds at their respective CD50 doses did not yield random or multiple of 180-200 bp DNA fragmentation which often associated with necrotic and apoptotic deaths respectively. Such observation may simply owe to the fact that the percentage of apoptosis and necrosis events were fairly low as quantified after acridine orangepropidium iodide staining, or may also suggest the involvement of sulphur residue in methylgerambullin and bis-(methylthiomethyl)-disulphide which act as an antioxidant, thus protecting DNA degradation from occuring. Flow cytometric analyses based on annexin V-FITC (fluorescein isothiocynate) binding to the phosphatidylserines residue which was translocated from the inner to the outer leaflet of the plasma membrane showed that the onset of apoptosis in both methylgerambullin- and bis-(methylthiomethyl)-disulphide-treated population was at 6 hours exposure. Both methylgerambullin and bis-(methylthiomethyl)disulphide induced GO/G1 arrest up to 48 hours and 24 hours respectively followed by arrest in the subsequent S phase.